The Influence of National Culture on Entrepreneurial Behaviour: The Case of Saudi Arabia - Alghamdi, Ahmed Yahya A (2008)
Entrepreneurship has been long hailed as one of the most important forces of driving economic growth. However, such endeavour is always confronted with several economical, political and cultural challenges that have impacts on entrepreneurs and the process of creating their ventures.